Scintigraphic Demonstration of Urine Extravasation Secondary to Acute Ureteral Obstruction: A Case Report and Some Considerations about Acute Ureteral Obstruction - Federico M. Sarmiento; Arístides J.H. Sarmiento; Edgardo Bardoneschi; Arístides H. Sarmiento (The Scientific World Journal)
Acute ureteral obstruction produces renal damage and complications that are proportional to the severity and length of the obstruction. Anatomic diagnosis of the obstruction may be insufficient to manage the patient. Intravenous urogram (IVU) is the method usually advised by radiologists to obtain functional information, but requires iodinated contrast agents. IVU anatomic information is superior to anatomic information obtained with renal scintigraphy, but normally the physician already has the anatomic information (unenhanced CT or ultrasound). A renal scan offers better physiologic information than the IVU, has neither adverse effects nor complications, is accurate to confirm or discard significant ureteral obstruction, and depicts obstruction complications. This paper presents a patient with spontaneous urine extravasation secondary to acute renal obstruction who is diagnosed with renal scintigraphy. The authors describe the scintigraphic signs of extraperitoneal, diffuse perinephric, urine extravasation and emphasize the role of renal scintigraphy in diagnosis and follow-up of renal colic.